(untitled) (Khairulummah, 2023)
Peace remains imperative for human beings and their prosperity and development at large.That’s why Islam is a great supporter of peace and it wants to wipe out all the factors and reasons that cause danger to peace. Most importantly, The word Islam means peace and security as well. A great number of Quranic verses and Hadiths mention the importance, establishment and precepts of peace. As wars and conflicts are the killer of peace.So,Islam gives clear and expressive teachings for eliminations of them and promotes international and global peace view for the safety, sanctity, protection and security of the world as a whole. I want to give brief overview of peace in light of Islamic view and outlook.